Great investment ideas - Ziemba, William T. (World Scientific series in finance, 2017)
This volume presents insights and strategies from prominent investment experts around the world. Covering topics such as portfolio management, asset allocation, financial modeling, and market behavior, it bridges academic finance and practical investment approaches to guide professionals and scholars alike.